Teaching Diversity, Advancing Democracy: Challenges for Citizenship Education in Aotearoa New Zealand - Tawhai, Veronica M.H. (The International Journal of Diversity in Organizations, Communities, and Nations: Annual Review, 2008)
The presence of diverse needs, interests and perspectives in society is a key measure of a healthy representative democracy. Learning about diversity, and how society provides for diversity, is therefore a valuable characteristic of citizenship education (Arthur and Davison, 2000; Berding and Miedema, 1998; Feinberg, Fields and Roberts, 1997). This paper presents the findings of recent research about citizenship education in Aotearoa (New Zealand). In particular, it explores what presence the notion of diversity has in New Zealand’s citizenship education programme (social studies). In New Zealand, the provisions for diversity are under constant political debate. This includes the provisions for indigenous political representation, such as the Maori parliamentary seats. The research utilized critical discourse analysis and content analysis methods. A review of the social studies curriculum revealed a strong focus on identity, culture and heritage in New Zealand, but an absence of material about how diversity is provided for in society. This includes the socio-political provisions for diversity in New Zealand’s democratic arrangements, such as guaranteed indigenous representation. The implications of this absence are discussed in terms of citizens’ understandings of democracy, equality, and the preparation of citizens to discuss these issues further.
Keywords: citizenship; civics; diversity; education; equality

Theorising representation in the Māori seats: The crucial role of accountability - Nissen, Sylvia; MacDonald, Lindsey Te Ata o Tu (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2017)
The guaranteed Mäori seats are a distinguishing and controversial feature of New Zealand’s democracy. In recent years, a number of reports, commentators and politicians have called for the seats to be abolished on the grounds that they are no longer “needed” in New Zealand’s proportional electoral system. These claims are usually grounded in principles of equality. This paper makes the opposite claim: that principles of equality create convincing and coherent justifications for the Mäori seats. Drawing on feminist theories of representation, particularly the work of Iris Marion Young, Melissa Williams and Anne Phillips, this paper argues that the Mäori seats provide crucial mechanisms of accountability that ensure the fidelity of Mäori representatives to their constituencies. This notion of accountability has been largely absent in debates about the Mäori seats and challenges arguments against the seats that are based solely on perceived “need” relative to proportionate presence.
Keywords: equality; identity; representation